"Magnitude of clinical benefit" of solid tumour drugs and their real-world application in the Austrian health care setting. (September 2020) - Grössmann, Nicole; Robausch, Martin; Willenbacher, Wolfgang; Wolf, Sarah; Simon, Judit; Wild, Claudia
Highlights: clinical benefit assessment of recently approved cancer drugs via the ESMO-MCBS. analyses of cancer treatments included in the Austrian hospital benefit catalogue. application of ESMO-MCBS assessed cancer drugs in the public inpatient sector. overview of most frequently applied cancer treatments in the Austrian inpatient sector. Abstract: Objective: Insufficient evidence for robust decision-making especially for cancer drugs increases the importance of systematic assessments of clinical benefits and the actual real-world application. Therefore, we aimed to assess the clinical benefit of recently approved solid cancer drugs in Europe and their real-world application in the Austrian inpatient setting and day-patient settings. Methods: Our data basis was Austrian routine inpatient data provided by the Main Association of Austrian Social Security Institutions. All adult patients diagnosed with cancer in a public Austrian hospital between 2012 and 2016 were included. The clinical benefit of originator solid cancer drugs approved by the European Medicines Agency between 2009 and 2016 was assessed by applying two versions (original versus adapted) of the Magnitude of Clinical Benefit Scale (MCBS) from the European Society of Medical Oncology (ESMO). Results: Only a minority of our investigated cancer indications met the criteria for meaningful clinical benefit (MCB) independently of the applied ESMO-MCBS version (original: n = 6/33, adapted: n = 3/33). The threshold for MCB was most commonly met by breast cancer drugs. Furthermore, ten cancer drugs with highly rated indications (ESMO-MCBS: 4–5/B-A) were not included in the Austrian hospital benefit catalogue until 2016. Moreover, our results demonstrate that just a few of the ten most frequently applied cancer therapies were part of our ESMO-MCBS analyses. Conclusion: Systematically collected solid real-world data can contribute to evidence-based reimbursement and disinvestment decisions and thereby improve equal access to health care across all nine Austrian federal states.